Population attributable fraction of modifiable risk factors for Alzheimer disease: A systematic review of systematic reviews - Hazar, Narjes (Iran J Neurol, 2016)
Background: Alzheimer’s disease (AD) is the most common type of dementia. Demonstrating the modifiable risk factors of AD can help to plan for prevention of this disease. The aim of the current review was to characterize modifiable cardiovascular risk factors of AD using existing data and determine their contribution in AD development in Iran and the world. Methods: The systematic search was done in Medline, Scopus, and Cochrane databases from inception to May 2014 to find systematic reviews or meta-analyses about association between AD and cardiovascular modifiable risk factors included diabetes, hypertension (HTN), physical inactivity, smoking, hypercholesterolemia, and overweight and obesity. The population attributable fraction (PAF) was calculated for these risk factors in Iran and the world. Results: Of 2651 articles, 11 were eligible for data extraction after assessing relevancy and quality. Diabetes mellitus (DM) type 2, smoking, physical inactivity, overweight and obesity were significantly associated with increased risk of AD. Physical inactivity with 22.0% and smoking with 15.7% had the highest PAF for AD in Iran and the world, respectively. Conclusion: Our findings demonstrated that modifiable cardiovascular risk factors could increase the risk of AD. Moreover, about one-third of AD cases were attributed to five modifiable risk factors.